Digital Marketing sebagai Strategi Peningkatan Pemasaran Produk UMKM Desa Cerme Kabupaten Kediri - Ukrowiyah, Ukrowiyah; Hidayati, Nuril; Septiana, Arsiqum Yogi; Salsabilla, Ikhda Aini; Khasanah, Luluk Ilmiyatul; Khairurozikin, Rizal; Maulana, M. Fiqri; Kurniawati, Azzahra Dwi; Fashihuddin, M. Wildan; Naimah, Alfi Durrotun; Islamia, Eka Wahyu; Mumtahanah, Ismi; Baiti, Ayu Nuril; Sa'adah, Dinatus; Khilmi, M. Zamzami Busyronul; Faizah, Amilatul; Kurniasari, Eva; Rochimah, Mita Aini; Chuluq, M. Fachril Hamid Husnil (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This service aims to provide the public with a related understanding digital marketing, and expand market reach, as well as strengthen the MSME business they run. The method used is ABCD (Asset Based Community Development), which focuses on utilizing locally owned assets for community development. The result of this service is an understanding of MSMEs (Micro, Small and Medium Enterprises) regarding digital marketing increased as evidenced by social media account ownership; Instagram, Facebook and Tiktok which are managed by BUMDES Cerme Village. This program is useful in expanding market reach, increasing income, and building identity or branding local products, so that Cerme Village products become increasingly well known and competitive. This is proven by an increase in traffic social media in the form of interactions with posts, both from account followers and non-followers.